The impact of citizenship on intermarriage: evidence from Italy - Bianca Balsimelli Ghelli; Giovanni Gallo (Global Labor Organization (GLO), 2025)
Acquiring citizenship is associated with better economic and social opportunities for immigrants. This paper examines how, in a country with a large fraction of migrants, marriage decisions respond to a change in the legal status of foreign residents. The variation in the relationship between citizenship status and the propensity for mixed marriages could be influenced by the dominance of either the assimilation hypothesis or the status exchange hypothesis. Using individual-level data from the populated municipality of Modena, Emilia- Romagna (Italy), we find that the assimilation hypothesis prevails: the more immigrants integrate into host countries, the more likely they are to marry natives. Specifically, our results show that acquiring citizenship not only increases the likelihood of marriage but also significantly boosts the formation of mixed couples.
Keywords: J12; J15; O15; 330; Citizenship; intermarriage; foreign population; administrative data